2021
DOI: 10.3390/genes12030400
|View full text |Cite
|
Sign up to set email alerts
|

TYK2 Promoter Variant Is Associated with Impaired Insulin Secretion and Lower Insulin Resistance in Japanese Type 2 Diabetes Patients

Abstract: Accumulating evidence has suggested that viral infection causes type 1 diabetes due to direct β-cell damage and the triggering of autoimmune reactivity to β cells. Here, we elucidated that the tyrosine kinase 2 (Tyk2) gene, encoding an interferon receptor signaling molecule, is responsible for virus-induced diabetes in mice, and its promoter variant confers a risk of type 1 diabetes in humans. This study investigated the relationship between a TYK2 promoter variant (TYK2PV) and insulin secretion in type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…IFNα, a type 1 interferon, induces HLA class I expression, ER stress markers, and inflammation in human β cells, and acts in coordination with IL-1β to elicit β-cell death [180]. Polymorphisms in TYK2, a type I interferon receptor signaling molecule, confer risk for the development of diabetes [181]. Mice carrying a mutant Tyk2 fail to respond to type I interferon appropriately, leading to a failed β-cell antiviral response and sensitization to virus-induced diabetes [182].…”
Section: Ifnγ and Ifnα Signaling In β-Cell Deathmentioning
confidence: 99%
“…IFNα, a type 1 interferon, induces HLA class I expression, ER stress markers, and inflammation in human β cells, and acts in coordination with IL-1β to elicit β-cell death [180]. Polymorphisms in TYK2, a type I interferon receptor signaling molecule, confer risk for the development of diabetes [181]. Mice carrying a mutant Tyk2 fail to respond to type I interferon appropriately, leading to a failed β-cell antiviral response and sensitization to virus-induced diabetes [182].…”
Section: Ifnγ and Ifnα Signaling In β-Cell Deathmentioning
confidence: 99%
“…The TYK2 gene located in 19p13.2 is associated with the cytoplasmic domain of type I and type II cytokine receptors, and is a component of both the type I and type III interferon signaling pathways [ 60 , 61 ]. The TYK2 gene has a critical importance in the etiology of autoimmune and inflammatory diseases, specifically type 1 and type 2 diabetes, due to its association with the pancreatic β-cell-specific suppression of cytokine response including IFN [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mediating interferon response in connection to resistance to various infections Mediating Th1-and Th17-type immune reactions [50,58,59] UBASH3A Downregulating the NF-kB signalling pathway upon T cell receptor stimulation, thus reducing the IL2 expression [46,60] A genetic link between T1D and T2D is of special interest as the associated loci for them were thought to be almost completely separated despite the partially shared phenotype. Newer studies, however, found several shared risk genes or genetic polymorphisms [59,[61][62][63][64]. Some of the genes located in shared risk loci interact to mutually regulate important islet functions that are disturbed by disease-associated variants, leading to β-cell dysfunction [61].…”
Section: Regulating the Effects Of Cytokines Inside β-Cells For Proap...mentioning
confidence: 99%